Political Education. The Global Education of Citizen through Active Citizenship - Puka, Edi (Studi sulla Formazione/Open Journal of Education, 2014)
The human being grows in relationship with others of its fellows, and it is by virtue of this relationship that it receives a particular cultural heritage and acquires its own identity, differentiating itself, finding its own space of freedom and autonomy allowing it to interact and extend its own network of relations. In such a dynamic of reciprocity, the man realizes himself as such as a conscious member of a “social body”, i.e. of a radical society in an organic human context, which has become nowadays a clearly planetary one, by virtue of the unpublished migration flows and obvious interdependence of the Planet. The education is a line of human civility and it causes that grounds of anonymity, fears, consumerism, prejudice, haste, indifference, abuse, insecurity, solitude, become grounds of hospitality, trust, sharing, security, friendship, and brotherhood. The patterns of political education having prevailed so far are: the academic model with its explanation and dissent in the abstract of a great deal of knowledge, and that of the laboratory, which tilts and leans over, even by moments of simulation, toward vital worlds of operational policy. It is now manifested a widespread social demand about the necessity to provide to everybody, but especially in the range of basic youth socio-political information, an equipment of historical and values’ nature, and by providing comparative elements on the different socio-political matrices and traditions, raising the incentive at a renewing and increasingly conscious commitment in the face of growing difficulties, inherent to the political perspectives disputed so far in the world. It is necessary to refocus and reestablish a political culture uniting the breath of the ideal with the reality of administrative experience, supporting this political culture with the contribution of a dynamic and open reflection, capable of understanding the reality.